Clinical features and risk factors of catheter removal among 1062 episodes of peritoneal dialysis‐associated peritonitis: A multicenter 7‐year study. Issue 3 (14th December 2022) - Liu, Shichen; Yang, Liming; Zhu, Xueyan; Zhang, Xiaoxuan; Meng, Lingfei; Li, Xinyang; Zhao, Jing; Zhuang, Xiaohua; Cui, Wenpeng
Abstract: Introduction: Studies focusing on catheter removal and the pathogenic spectrum of peritoneal dialysis‐associated peritonitis (PDAP) need to be updated. Methods: Data were collected from four peritoneal dialysis (PD) centers. Peritonitis rates were compared using Poisson regression and Logistic regression was used to examine the risk factors for catheter removal. Results: The PD duration (odds ratio [OR], 1.021; 95% confidence interval [CI], 1.010–1.032), number of previous PDAP episodes (OR, 1.267; 95% CI, 1.039–1.545), dialysate white cell count >100 × 10 6 /L on Day 5 of PDAP (OR, 6.088; 95% CI, 3.277–11.312), Pseudomonas aeruginosa (OR, 4.122; 95% CI, 1.071–15.874) and polymicrobial infections (OR, 3.257; 95% CI, 1.519–6.982) were independent predictors of catheter removal ( p < 0.05). The prevalence of polymicrobial peritonitis and fungal peritonitis has increased ( p < 0.05). Conclusion: Attention should be paid to patients with long PD duration or a history of previous episodes of PDAP characteristics.